2006
DOI: 10.1111/j.1365-2036.2006.02858.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: intestinal serotonin signalling in irritable bowel syndrome

Abstract: SUMMARYAlterations in motility, secretion and visceral sensation are hallmarks of irritable bowel syndrome. As all of these aspects of gastrointestinal function involve serotonin signalling between enterochromaffin cells and sensory nerve fibres in the mucosal layer of the gut, potential alterations in mucosal serotonin signalling have been explored as a possible mechanism of altered function and sensation in irritable bowel syndrome. Literature related to intestinal serotonin signalling in normal and pathophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
138
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(141 citation statements)
references
References 60 publications
3
138
0
Order By: Relevance
“…Studies have found that alterations of many elements in the gastrointestinal mucosa serotonin (5-HT) signaling pathway occurs in IBS patients [6] , and this was one of the mechanisms for the disrupted visceral sensation and gastrointestinal motility in IBS patients. It has been shown that mast cells also play a role in the visceral hypersensitivity of IBS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that alterations of many elements in the gastrointestinal mucosa serotonin (5-HT) signaling pathway occurs in IBS patients [6] , and this was one of the mechanisms for the disrupted visceral sensation and gastrointestinal motility in IBS patients. It has been shown that mast cells also play a role in the visceral hypersensitivity of IBS patients.…”
Section: Introductionmentioning
confidence: 99%
“…5-HT acts on the 5-HT 3 receptors on the parasympathetic ganglia to cause smooth muscle contraction and increased intestinal secretion by stimulating nerve terminal acetylcholine release [5]. 5-HT 3 receptor antagonists inhibit the activation of 5-HT 3 receptors on the mucosal processes of the intrinsic and extrinsic primary afferent neurons and attenuate motor and secretory reflex activity while decreasing the depolarization of extrinsic sensory neurons that transmit signals to the brain, thereby inhibiting the sensory signals leading to abdominal pain and discomfort and are likely directly or indirectly related to the pathophysiology of IBS [6]. This has been exploited therapeutically in patients with IBS-D in whom 5-HT 3 receptor antagonists improve gastrointestinal (GI) symptoms, reducing stool frequency, urgency, and abdominal discomfort while increasing stool consistency [7].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, patients with IBS visit physicians more often, consume more medications and undergo more diagnostic tests than non-IBS patients. 8,9 While the aetiology of this disorder remains obscure, there is a body of evidence suggesting dysregulation of several pathophysiological pathways including serotonin biosynthesis and metabolism, [10][11][12] mast cell infiltration and degranulation, [13][14][15][16][17] visceral hypersensitivity, an exaggerated stress response, immune activation and bacterial infection (post-infectious IBS) or microbiota alterations. [18][19][20][21][22] Gene expression profiling in tissue samples taken from patients with IBS has been reported using sigmoid colonic mucosal tissue.…”
Section: Introductionmentioning
confidence: 99%